Persepsi Siswa SMP Negeri 35 Banjarmasin Terhadap Pernikahan Usia Dini - Permatasari, Rahmah; Puji Hastuti, Karunia; Muhaimin, Muhammad; Adyatma, Sidharta; Alviawati, Eva (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
Early marriage in adolescents can have an impact on adolescent health, both physically and psychologically. The causes of early marriage are influenced by various factors, namely factors that arise within themselves and also from outside themselves. This research is entitled